Large scale synthesis and uses of a cobalt based metal - organic framework compound as liquid water sensor - Sharma, Nayuesh (My University, 2013)
Metal−organic frameworks (MOFs) comprised of inﬁnite networks of metal centers or inorganic clusters bridged by simple organic linkers through metal−ligand coordination bonds. We have synthesized a cobalt based metal – organic network on gram scale. We have shown that it is sensitive to liquid water but not to water vapor. We have also compared its sensitivity with CoCl2.6H2O. The compound (original and dehydrated) is not soluble in water and is lighter than CoCl2.6H2O.The dehydrated compound can be used as liquid water sensor in presence of water vapor.
Master of Science-Chemistry, Dissertation
Keywords: Metal−organic frameworks (MOFs); powder X – ray; sensor; thermogravimetric analysis (TGA)